Tumour necrosis factor related apoptosis inducing ligand (TRAIL) induces hepatic steatosis in viral hepatitis and after alcohol intake. Issue 11 (13th October 2005) - Mundt, B; Wirth, T; Zender, L; Waltemathe, M; Trautwein, C; Manns, M P; Kühnel, F; Kubicka, S
Abstract : Background and aims: Tumour necrosis factor related apoptosis inducing ligand (TRAIL) induces apoptosis in transformed cells and is considered as an agent for cancer therapy. As there is evidence that TRAIL is also essential for apoptosis in animal models of liver injury, we investigated the role of TRAIL in viral hepatitis and after alcohol consumption. Methods: Expression of TRAIL was determined by western blot analysis in the liver of patients with chronic hepatitis C virus (HCV) infection as well as in experimental acute adenoviral hepatitis and after alcohol intake in the liver of mice. To investigate the effect of FasL and TRAIL expression, we used low dose adenoviral gene transfer. Apoptosis and steatosis were assessed by TUNEL and fat red staining, and by caspase assays. Results: TRAIL was overexpressed in the liver of patients with HCV associated steatosis while acute adenoviral hepatitis resulted in upregulation of TRAIL-DR5. In contrast with FasL, TRAIL expression was harmless to healthy livers. However, in virally infected livers, TRAIL expression induced apoptosis and steatosis whereas expression of FasL only resulted in apoptosis of hepatocytes without steatosis. After alcohol intake, TRAIL expression led to hepatic steatosis, without apoptosis of hepatocytes, indicating that TRAIL mediated apoptosis and steatosis may be independently modulated after viral infection and alcohol intake. In viral hepatitis and after alcohol intake, Ad-TRAIL mediated steatosis can be inhibited by injection of a neutralising TRAIL antibody. Conclusions: We identified TRAIL as a new mediator of hepatic steatosis in viral hepatitis and after alcohol intake. Consequently, TRAIL mediated hepatotoxicity has to be considered in patients with viral hepatitis and alcoholic liver disease.